Astragalus membranaceus and Panax notoginseng saponins improves intestinal l-arginine absorption and protects against intestinal disorder in vivo - Huang, Su-Fen; Shen, You-Cheng; Ou, Ching-Hui; Tang, I-Chu; Yang, Han-Wen; Kao, Yu-Ting; Chang, Wen-Liang; Chang, Tsu-Chung (Food Science and Technology Research, 2023)
Nutritional supplementation with l -arginine has been shown to promote cell growth and exercise performance, and is helpful to various disorders. Astragalus membranaceus and Panax notoginseng are traditional herbal medicines that display a wide range of beneficial activities. To understand their effects on l -arginine absorption in human intestinal cells, in vitro and in vivo experiments were performed using a standardized mixture of Astragalus membranaceus and Panax notoginseng saponins (APS). Our studies indicated that APS increased the expression of cationic amino acid transporter 1 (CAT1) and L- arginine transport in human Caco-2 cells. In addition, APS benefits TNBS-induced-colitis rats by increasing food intake, body weight, intestinal epithelial integrity, CAT1 gene expression, and blood l -arginine level. APS also reduces intestinal inflammation associated with increased myeloperoxidase activity in colitis rats. Further studies indicated that the plasma l -arginine level significantly increases in human subjects administered APS.